PENGARUH LEVERAGE KEUANGAN TERHADAP TINGKAT AKTIVITAS INVESTASI BANK (Studi Kasus Perbankan yang terdaftar di Bursa Efek Indonesia Periode 2012-2015) - Gita Rachma; Deni Syachrudin (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2017)
The main objective of this research was to analyze the correlation between financial leverage and investment activities of the banking. DAR (Debt to Asset Ratio), DER (Debt to Equity Ratio), and LDER (Long term Debt to Equity Ratio) were the variables that used as the indicator of financial leverage. TATO (Total Asset Turnover) is the variable that used as the indicator of investment activity of the banking. This research was an associative explanation research where the variables had causality characteristic. The sample was banking listed on the Stock Exchange were selected by purposive sampling method. The data used are time series, and is taken from the annual financial statements of the banking years 2012 to 2015. Hypothesis testing is done by the statistical method through analysis of correlation. The results showed that there was indeed a significant correlation between financial leverage and investment activity of the company based on agency theory. The most strength correlation was state in DER had possitive and significant correlation to TATO